Nyai Ontosoroh: a Female Hero and Her Resistance to Gender Injustice - Budi Waluyo; Andrik Purwasito; Warto Warto; Slamet Subiyantoro (Jurnal Lingua Idea, 2021)
Nyai Ontosoroh is a character in Pramudya Ananta Toer's novel Bumi Manusia, which depicts a woman's struggle against injustice in her life. R. Giryadi adapted Nyai Ontosoroh's struggle in this novel into a short drama titled "Nyai Ontosoroh." The plot of this drama revolves around Nyai Ontosoroh's opposition to her husband and the Dutch government, which wants to take over the company and custody of her child. A Javanese woman's resistance to the colonial government was courageous at the time. Despite being defeated, Nyai Ontosoroh had fought for his rights in a dignified manner. She deserved to be referred to as a "hero." The purpose of this study is to explain and describe the various forms of gender injustice against women in R. Giryadi's drama script "Nyai Ontosoroh." This study is descriptive qualitative in nature. It is tailored to the formulation of determined research problems. It is a qualitative study that is thoroughly and analytically described. Forms of gender injustice against women are described. The conclusion of this paper indicates that women in Indonesia continue to face numerous gender injustices. Women must fight for gender equality as they should.